A Philosophical Systems Engineering Perspective of Energy Storage for Electric Grids - Ribeiro, Paulo (Advanced Technologies Journal of University of Benghazi, 2026)
Energy storage has become an essential enabler of resilience, stability, and flexibility in today's electric grids. While standardized by some nominal measures, such as power capacity, energy density, and cost, the advanced storage technologies paved the way for wider requirements of system engineering that goes beyond their technical performance. This paper introduces a philosophical system engineering perspective of energy storage, viewing it as an approach of shaping time within complex power system architectures rather than simply storing energy. Relying on practical experience from large-scale military and utility applications, the analysis emphasizes lifecycle, integration, interoperability, degradation, and end-of-life management as major determiners of storage value. It is stated that no single storage technology can address the diverse requirements of the energy transition. Instead, future electric grids must rely on carefully engineered portfolios of complementary storage technologies, designed using systems engineering principles. The paper concludes that the primary challenge of energy storage is architectural rather than technological, requiring grids to be designed with temporal intelligence to balance immediacy, reliability, resilience, and long-term sustainability.